Pentingnya Kenyamanan Belajar Dan Mengajar Dalam Islam Serta Relevansinya Dengan Tafsir Al-Qur’an Surat Al-Mudallah Ayat 11 - Amri, Almer Ragil; Az - Zahra, Muthia; Azzahra, Intan Nuraini; Wismanto, Wismanto (STAI Denpasar Bali, 2024)
Islam teaches that humans are obliged to seek knowledge, so teaching and learning activities are a process of activities carried out by humans, both formal and informal learning. This research aims to show the relevance of comfort in learning and teaching in Islam in the context of verse 11 of the Al-Quran Surah Al-Mujjadi. There this verse is discussed in relation to Islam and comfort in Islam. The learning and teaching process is interpreted. This research uses library research, where all the main data in this research comes from books, magazines, tafir books and journals related to the theme of this research. The research results show that there is a relationship between the comfort of the teaching and learning process by educators with verse 11 of Surah Mujjadi. This is closely related to the environment, facilities and infrastructure that support learning and educational activities. Through interaction and connection between teachers and students, even at the end of the verse it is stated that Allah will raise the status of those who believe and have knowledge.